The complete mitochondrial genome of the toad species Oreolalax xiangchengensis (Anura: Megophryidae) and phylogenetic analyses. Issue 2 (3rd July 2018) - Li, Shize; Gao, Xinyu; Wei, Gang; Wang, Bin; Xu, Ning
Abstract: Oreolalax xiangchengensis is an alpine toad species of Megophryidae. We determined its complete mitogenome. The mitogenome has a length of 17, 110 bp, containing 13 protein-coding genes, 2 rRNA genes, 23 tRNA genes, and a control region. It has a tandem duplication of tRNA-Met gene and a translocation of tRNA-Trp gene compared with typical vertebrate mitogenomes. Phylogenetic analyses based on the mitogenome sequences of 18 Megophryidae species were conducted to access phylogenetic assignments of O. xiangchengensis .